2022
DOI: 10.3390/ijerph19063728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Classical Breathing Exercises on Posture, Spinal and Chest Mobility among Female University Students Compared to Currently Popular Training Programs

Abstract: Worldwide, university students’ physical health and posture are declining due to a sedentary lifestyle. The aim of our study was to evaluate the effectiveness of physiotherapeutic breathing exercises on posture and spinal mobility among healthy female university students compared to other training methods. Sixty-one female students of the University of Debrecen were assigned to breathing exercise (BE; n = 15), yoga (Y; n = 16), Pilates (P; n = 15) programmes and interval-training (IT; n = 15). Each training se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…One of the most common complications of scoliosis is the development of respiratory problems. Studies have shown that physiotherapy techniques, such as controlled breathing exercises and respiratory muscle training, can upgrade respiratory function [91][92][93]. Furthermore, wearable respiratory sensors and biofeedback techniques can effectively monitor and manage respiratory function in patients with scoliosis [94][95][96].…”
Section: Diagnostic Techniques Treatment Strategies and Management Me...mentioning
confidence: 99%
“…One of the most common complications of scoliosis is the development of respiratory problems. Studies have shown that physiotherapy techniques, such as controlled breathing exercises and respiratory muscle training, can upgrade respiratory function [91][92][93]. Furthermore, wearable respiratory sensors and biofeedback techniques can effectively monitor and manage respiratory function in patients with scoliosis [94][95][96].…”
Section: Diagnostic Techniques Treatment Strategies and Management Me...mentioning
confidence: 99%
“…In recent years, a growing number of studies have proved that breathing exercises can significantly improve the quality of life (Yiting, Zile, Wang, Xuanlin, & Yang, 2022). Research suggests that breathing exercises can be safely used and may have positive effects on the posture, flexibility, and strength of healthy adults (Csepregi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Pilates is a unique training system that was created in the early 20th century by a German named Joseph Pilates [14]. Pilates mainly trains deep core muscles, including transversus abdominis, diaphragm, abdominal oblique muscles, multifidus, and pelvic floor muscles, to enhance core muscles strength and endurance, maintain and improve somatic motor nerve control, increase spinal control, and improve somatic stability [15][16][17].…”
Section: Introductionmentioning
confidence: 99%